Low-oxygen pulping combined with high hydrostatic pressure improve the stability of blueberry pulp anthocyanins and color during storage. (August 2022) - Zhang, Lijuan; Xiao, Gengsheng; Yu, Yuanshan; Xu, Yujuan; Wu, Jijun; Zou, Bo; Li, Lu
Abstract: Anthocyanins is susceptible and easily affected by temperature and oxygen. Conventional pulping and pasteurisation treatment usually has negative impacts on color and anthocyanins of blueberry pulp. This study was to comparatively evaluate the effects of low-oxygen and conventional pulping combined with high hydrostatic pressure (HHP: 500 MPa/5 min) and pasteurisation (PAS: 85 °C/15 min) processing on color and anthocyanins of blueberry pulp. The degradation kinetics of total anthocyanins and individual anthocyanins during storage at 4 °C were also studied. Results showed that the degradation kinetics of individual anthocyanins was consistent with those of total anthocyanins, which followed the first-order kinetic model, except for Delphinidin-3-glucoside and Peonidin-3-galactoside, which followed the zero-order kinetic model. The half-life time (t1/2 ) of total anthocyanins in four different treatments was as follows: low-oxygen pulping (LP) + HHP > LP + PAS > conventional pulping (CP) + HHP > CP + PAS. Compared with the other three groups, LP + HHP could better protect the color of blueberry pulp during storage. The total contents of phenolics and anthocyanins in LP + HHP were higher than that in CP + HHP after storage. In summary, LP + HPP treatment effectively kept the color and anthocyanins of blueberry pulp.